Warming Disadvantages Phytoplankton and Benefits Bacteria During a Spring Bloom in the Mediterranean Thau Lagoon - Courboulès, Justine; Mostajir, Behzad; Trombetta, Thomas; Mas, Sébastien; Vidussi, Francesca (Frontiers in Marine Science, 2022)
To assess the response of a natural plankton community to the future scenario of a warming of +3 °C predicted for coastal Mediterranean regions, an in situ mesocosm experiment was carried out over 19 days in a Mediterranean coastal lagoon in 2018. During this experiment, a phytoplankton bloom occurred and the abundances of several cytometric groups of phytoplankton (cyanobacteria, picophytoplankton and nanophytoplankton) and bacteria (low- and high-nucleic acid bacteria), as well as their growth and grazing mortality rates and their carbon biomass, were studied over the course of the experiment. Experimental warming led to a significant reduction of 47% of the phytoplankton biomass in average, based on Chl-a concentrations. This reduction was also observed for nanophytoplankton abundances during the whole experiment and for eukaryotic picophytoplankton only during the bloom period. This result coincided with a significant decrease in orthophosphate concentrations under warming during the prebloom and bloom periods simultaneous to an increase in bacterial abundances. At the same time, the higher growth rates of bacteria and the lower ones of phytoplankton observed at the beginning of the bloom could suggest that competition between phytoplankton and bacteria for orthophosphate might have contributed to the phytoplankton biomass decrease under warming. In addition, higher grazing mortality rates of phytoplankton groups under warming, notably nanophytoplankton at the end of the bloom and in postbloom (by 59 to 626%), as well as eukaryotic picophytoplankton over the course of the experiment (by 58 to 255%) could also have contributed to the lower phytoplankton biomass under warming. Based on these results, estimations of average phytoplankton carbon biomass production and transfer showed reductions of 42 and 45%, respectively, under warming, whereas those of bacteria were enhanced by 13 and 8%, respectively. These results indicated that warming induced a shift at the base of the microbial food web, going toward a more bacteria-based system. This suggested that under future warming scenarios, the microbial food web could become less productive and could negatively affect the functioning of the whole food web in coastal waters.